Barriers to ESC guideline implementation: results of a survey from the European Council on Cardiovascular Nursing and Allied Professions (CCNAP) - McKee, Gabrielle; Kerins, Mary; Hamilton, Glenys; Hansen, Tina; Hendriks, Jeroen; Kletsiou, Eleni; Lambrinou, Ekaterini; Jennings, Catriona; Fitzsimons, Donna (My University, 2017)
Background: The European Society of Cardiology (ESC) has a comprehensive clinical guideline development programme, relevant for all clinicians. However, implementation of guidelines is not always optimal. Aim: The aim of this study was to determine nurses’ and allied professionals’ awareness and barriers regarding clinical guideline implementation. Methods: A cross-sectional survey was administrated online and in print at EuroHeartCare 2015. A questionnaire was developed which examined awareness and barriers to implementation of ESC guidelines on cardiovascular disease prevention in clinical practice (2012) and ESC guidelines in general. Results: Of the 298 respondents, 12% reported that the prevention guidelines were used in their practice area. Respondents identified, in order of magnitude, that lack of leadership, workload, time, resources and a perception that they were unable to influence current practice were barriers to the use of the prevention guidelines. When asked to rank barriers to use of any ESC guidelines, time (22%) and leadership (23%) were ranked highest. Conclusions: Implementation of ESC guidelines by nurses, the majority responders in this survey, is a serious problem, requiring urgent improvement to ensure patients receive optimal evidence based care. Issues of leadership, workload, time and resources are significant barriers to guideline implementation. It is of concern that these professionals perceive both that they have little influence on implementation decisions and lack of leadership regarding guideline implementation. Educational and organisational strategies to improve leadership skills are imperative. These will build self-efficacy and empower nurses and allied professionals to advocate for evidence-based care in the clinical environment.
Keywords: Barriers; Cardiac patients; Clinical guidelines; Implementation; Prevention